Perbandingan Kadar Pati Pada Beras Hitam Dibandingkan Dengan Beras Putih Menggunakan Uji Iodida - Yoviono, Firza; Sandra, Yurika; Arifandi, Firman (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Diabetes mellitus (DM) is a metabolic disease that causes elevated blood sugar levels. This may be due to excessive carbohydrate intake. Carbohydrates are an important part of the human diet. Carbohydrates not only meet the basic needs of the body, but are also the body’s main source of energy, and the most widely consumed carbohydrate in Indonesia is starch or rice starch. There are many types of rice such as white rice and black rice. This study aims to compare the starch content of white black rice and use the iodide test to determine the best type. White rice (Oryza Sativa L. Indica) and black rice (Oryza Sativa L. Indica)) were used for descriptive analysis, and iodide was used to test the sensitivity of these samples). Starch content test. Data were analyzed using t-test to compare the starch content of white rice and black rice. The results showed that the starch content of white rice was 24.47 mg/100 mg (24.47%), while the starch content of black rice was 16.94 mg/100 mg (16.94%). The statistical t test then gave a p value <0.05. This shows that the starch content of white rice and brown rice is significantly different. The results showed that white rice has a higher starch content than black rice.